CFD Modeling of Heat Sinks Under Realistic Operating Conditions (Jóvenes en la Ciencia, 2015)
As the power density of integrated circuits has increased, requiring heat sinks to be smaller, they have to be capable of dissipating greater heat fluxes. However, the majority of integrated circuit failures result from thermal activated processes. In this paper, we present a heat sink for cooling the processor of a desktop computer used for research purposes. The heat sink uses a liquid as a working fluid as opposed to air like conventional heat sinks. Different operating conditions of the computer are simulated by changing the volumetric flow rate of the working fluid to analyze the performance of the heat sink under those operating conditions. The models are simulated using a commercial CFD program. Additionally, we study the mesh quality of the model using a heat flux of 100 kW/m^2 applied to the base of the heat sink. Results show that with 360,000 elements, grid independence is achieved. Furthermore, using 360,000 elements helps reduce computational time. Finally, the results illustrate that the thermal performance of the heat sink is improved at higher volumetric flow rates with a maximum outlet fluid temperature increase of 9 K at 4.17x10^-4 m^3/s.
Keywords: Array; Array; Array; Array